Exploring Middle School Students' Attitudes and Engagement in Coding: An Analysis of Interest, Motivation, Confidence, and Anxiety (International Journal of Environmental Sciences, 2025)
In today’s fast-paced digital world, knowing how to code has become a crucial skill for everyone, not just those aiming for tech careers. As society becomes more digital, understanding coding can help people navigate this new landscape more effectively. This study focuses on the attitudes of middle school students, aged 11 to 14, toward coding, examining their interest, motivation, confidence, and anxiety. For this study, we involved 80 students from schools in Ghaziabad, Uttar Pradesh, India, using a mix of research methods and randomly choosing the participants. The data we gathered from surveys showed that most students have a generally positive view of coding. Students showed different levels of interest, motivation, and confidence, and some felt quite anxious about coding tasks. This suggests that it’s crucial to create a learning environment that supports and encourages them, helping to build a more positive attitude toward coding. It also points to the necessity for strategies that can boost student engagement and help ease any anxiety they may have about learning to code. By addressing these needs, educators, curriculum developers, and policymakers can find more effective ways to teach coding in middle schools, better preparing students for the increasingly digital world they are entering.